Normocephalic Children Exposed to Maternal Zika Virus Infection Do Not Have a Higher Risk of Neurodevelopmental Abnormalities around 24 Months of Age than Unexposed Children: A Controlled Study - Juannicelle T. A. M. Godoi; Silvia F. B. M. Negrini; Davi C. Aragon; Paulo R. H. Rocha; Fabiana R. Amaral; Bento V. M. Negrini; Sara R. Teixeira; Aparecida Y. Yamamoto; Heloisa Bettiol; Marisa M. Mussi-Pinhata (Pathogens, 2023)
Although very few controlled studies are available, in utero Zika virus (ZIKV)-exposed children are considered at risk for neurodevelopmental abnormalities. We aimed to identify whether there is an excess risk of abnormalities in non-microcephalic children born to mothers with confirmed ZIKV infection compared with ZIKV-unexposed children from the same population. In a cross-sectional study nested in two larger cohorts, we compared 324 ZIKV-exposed children with 984 unexposed controls. Outcomes were assessed using the Bayley Screening Test III applied around 24 months of age. Relative risks for classifying children as emergent or at-risk for neurodevelopmental delay in at least one of five domains were calculated, adjusting for covariates. In four of the five domains, few children were classified as emergent (4–12%) or at-risk (0.3–2.16%) but for the expressive communication domain it was higher for emergent (19.1–42.9%). ZIKV-exposed children were half as frequently classified as emergent, including after adjusting for covariates [RR = 0.52 (CI 95% 0.40; 0.66)]. However, no difference was detected in the at-risk category [RR = 0.83 (CI 95% 0.48; 1.44)]. Normocephalic children exposed to the Zika virus during pregnancy do not have a higher risk of being classified as at risk for neurodevelopmental abnormalities at two years of age.